Corporate social irresponsibility: humans vs artificial intelligence. Issue 6 (12th December 2018) - Krkač, Kristijan
Abstract : Purpose: The supposedly radical development of artificial intelligence (AI) has raised questions regarding the moral responsibility of it. In the sphere of business, they are translated into questions about AI and business ethics (BE) and corporate social responsibility (CSR). The purpos of this study is to conceptually reformulate these questions from the point of view of two possible aspect-changes, namely, starting from corporate social irresponsibility (CSI) and starting not from AIs incapability for responsibility but from its ability to imitate human CSR without performing typical human CSI. Design/methodology/approach: The author draws upon the literature and his previous works on the relationship between AI and human CSI. This comparison aims to remodel the understanding of human CSI and AIs inability to be CSI. The conceptual remodelling is offered by taking a negative view on the relation. If AI can be made not to perform human-like CSI, then AI is at least less CSI than humans. For this task, it is necessary to remodel human and AI CSR, but AI does not have to be CSR. It is sufficient that it can be less CSI than humans to be more CSR. Findings: The previously suggested remodelling of basic concepts in question leads to the conclusion that it is not impossible for AI to act or operate more CSI then humans simply by not making typical human CSIs. Strictly speaking, AI is not CSR because it cannot be responsible as humans can. If it can perform actions with a significantly lesser amount of CSI in comparison to humans, it is certainly less CSI. Research limitations/implications: This paper is only a conceptual remodelling and a suggestion of a research hypothesis. As such, it implies particular morality, ethics and the concepts of CSI and AI. Practical implications: How this remodelling could be done in practice is an issue of future research. Originality/value: The author delivers the paper on comparison between human and AI CSI which is not much discussed in literature.